Male and Female Adult Population Health Status in China: A Cross-Sectional National Survey - Lu Mingshan; Zhang Qiuju; Liu Meina; Shi Jing; Quan Hude (BMC Public Health, 2008)
Abstract Background With rapid economic growth and globalization, lifestyle in China has been changing dramatically. This study aimed to describe the male and female adult Chinese population health status. Methods The Chinese Third National Health Services Survey was conducted in 2003 to collect information about health status and quality of life from randomly selected residents. Of the 193,689 respondents to the survey (response rate 77.8%), 139,831 (69,748 male and 70,083 female) respondents who were 18 years of age or older were analyzed. Results Among the respondents, fewer males than females rated their overall wellbeing as being poor or very poor (4.8% versus 6.2%), reported illness in the last 2 weeks (14.1% versus 17.4%), presence of physician diagnosed chronic disease (15.0% versus 17.7%) and at least one functional problem in seven items of the quality of life (26.9% versus 32.8%). More males than females were currently smoking (52.4% versus 3.4%) and drank alcohol more than three times per week (16.5% versus 1.1%). Physically inactive rate was similar between males and females (85.8% versus 87.0%). Fewer rural respondents reported chronic disease than urban respondents (13.0% versus 19.9% for males and 15.5% versus 22.8% for females). In all seven items of the quality of life measured, rural respondents reported less problems than urban respondents (26.2% versus 28.7% for males and 32.0% versus 34.7% for females). Conclusion Males had better health status than females in terms of self-perceived wellbeing, presence of illness, chronic disease, and quality of life. However, smoking and frequent alcohol drinking was more prevalent among males than that among females. In contrast with the social-economic gradient in health commonly found in the literature, the wealthier urban population in China was not found to be healthier than the rural population in terms of physician diagnosed chronic disease.